Perbandingan Efektivitas Berkumur Susu Sapi dan Susu Kedelai Kemasan Terhadap Penurunan pH Saliva - Zulkaidah, Utari; Arsad, Arsad; Dirman, Rezki; Yulistina, Yulistina; Oktasulfya, A. Nun Ashty (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Saliva plays a major role in maintaining the balance of the oral cavity ecosystem through its ability to remineralize and control bacterial activity. One factor that can affect the pH of saliva is the type of food and drink consumed, including milk. Cow's milk and soy milk can cause a decrease in the acidity (pH) of saliva because milk contains some acidic substances. Purpose of the study: To determine the effectiveness of gargling cow's milk and packaged soy milk on the reduction of saliva pH of grade XI students at SMAN 03 Bombana, Southeast Sulawesi Province. Research method: The method used is quantitative experiment using pre-test and post-test design. Research Results: Based on the results of the study, it was found that the mean pH value of saliva after gargling packaged cow's milk was 5.59 ± 0.2269, while the mean pH value of saliva after gargling soy milk was 5.73 ± 0.1899. Thus, it was proven that the decrease in saliva pH was more significant after gargling using soy milk compared to cow's milk. The results of the study also showed that there was an effectiveness in reducing the pH of saliva in gargling cow's milk and packaged soy milk p = 0.000 (p˂0.05). Based on the results of the study, it can be concluded that gargling cow's milk and packaged soy milk can lower the pH of saliva. The decrease in saliva pH was more significant after gargling packaged soy milk than gargling packaged cow's milk.